An Examination of the Association between Difficulties with Emotion Regulation and Dating Violence Perpetration - Shorey, Ryan C. (2011)
The perpetration of aggression in dating relationships is a prevalent problem among college students. Research that examines factors related to perpetrating dating violence is needed, as this could help guide prevention programming. This study examined how emotion regulation is related to dating violence perpetration among male and female college students (N = 440). Findings showed that the association between broad difficulties with emotion regulation, as well as more specific emotion regulation problems, were associated with dating violence perpetration and could differentiate individuals who had perpetrated and not perpetrated aggression. These findings varied slightly depending on the gender of the perpetrator and the type of aggression examined. Implications of these findings for prevention programs and future research are discussed.